Evaluating Sin Stocks' Performance on the London Stock Exchange : Empirical evidence compared to the FTSE All-Share Index - Serlenius, Niklas (My University, 2024)
This thesis evaluates the performance of sin stocks, defined as companies operating in industries like tobacco, alcohol, and gambling, on the London Stock Exchange (LSE) from 2013 to 2023, compared against the FTSE All-Share Index. It investigates whether these stocks collectively outperform the market and evaluates the performance of the individual sin industries. In this study, a quantitative approach was applied, using established risk-adjusted metrics to evaluate the performance of sin stocks listed on the London Stock Exchange. The Treynor Ratio and Sharpe Ratio were calculated using standard methods. Additionally, a regression analysis was applied to determine Jensen’s Alpha and beta for the sin industry portfolios. The key findings of the analysis revealed diverse outcomes across the different industries. The gambling sector demonstrated superior performance in terms of risk-adjusted returns, outperforming both the broader market index and other sin industries. Conversely, the tobacco industry and the total sin portfolio underperformed relative to the market. The alcohol sector exhibited a consistent outperformance against the market index, highlighting the variable nature of investment returns within sin stocks. The study contributes to the academic discussion on the balance between ethical considerations and investment performance, particularly within controversial sectors. It suggests that while some sin investments may offer attractive returns, their performance can be highly variable and dependent on the industry. This study highlights the complexity of investing in sin stocks and the importance of considering ethical impacts alongside financial returns.

Tässä kandidaatintyössä tutkitaan syntiosakkeiden suoriutumista Lontoon pörssissä vuosien 2013 ja 2023 välillä. Syntiosakkeiksi luokitellaan yritykset, jotka toimivat esimerkiksi tupakka-, alkoholi-, ja uhkapeliteollisuudessa. Tutkimuksessa selvitetään, miten syntiosakkeet ovat suoriutuneet riskikorjatuilla mittareilla suhteessa markkinaindeksiin, joka on tässä tutkimuksessa FTSE All-Share -indeksi. Tutkimuksessa hyödynnettiin kvantitatiivista menetelmää, ja syntiosakkeista muodostettuja painotettuja portfolioita arvioitiin vakiintuneiden riskikorjattujen mittareiden avulla. Sharpen ja Treynorin luvut laskettiin standardimenetelmällä syntiportfolioille, ja lisäksi regressioanalyysillä selvitettiin Jensenin alfa ja beeta. Analyysin tulokset osoittivat, että eri toimialojen tulokset vaihtelivat suuresti. Uhkapeliosakkeista muodostettu portfolio erottui edukseen tarjoamalla parhaat riskiin suhteutetut tuotot suoriutumalla paremmin kuin markkinaindeksi ja muut syntiportfoliot. Sen sijaan tupakkatoimiala sekä kolmesta syntitoimialasta muodostettu kokonaisportfolio suoriutuivat huonommin kuin markkinaindeksi. Tämä tutkimus tarjoaa näkökulmia akateemiseen keskusteluun eettisten näkökohtien ja sijoitustuottojen välillä. Tämä osoittaa, että vaikka osa syntitoimialoista tarjoaa houkuttelevia tuottoja verrattuna markkinaan, niiden menestys vaihtelee suuresti toimialasta riippuen. Tutkimus korostaa syntiosakkeisiin sijoittamisen monimutkaisuutta ja eettisten seikkojen huomioon ottamisen merkitystä taloudellisten tuottojen ohella.
Keywords: sin stock, risk-adjusted measure, Treynor ratio, Sharpe ratio, Jensen’s alpha, regression analysis, London stock exchange, syntiosake, riskikorjattu tunnusluku, Treynorin luku, Sharpen luku, Jensenin alfa, regressioanalyysi, Lontoon pörssi